Spontaneous Aneurysmal Subarachnoid Hemorrhage and Related Cortisol and Immunologic Alterations: Impact on Patients' Health-related Quality of Life - Ridwan, Sami; Greschus, Susanne; Boström, Jan; Barrera, Julio; Esche, Jonas; Zur, Bernd; Klingmüller, Dietrich; Boström, Azize (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Objective To highlight the impact of aneurysmal subarachnoid hemorrhage (SAH) on surviving patients' health-related quality of life (HRQoL) with respect to cortisol and interleukin (IL)-6 alterations and also to identify possible clinical predictors for a better HRQoL.Methods Fifty surviving patients treated in our hospital for aneurysmal SAH in a 2-year period with sufficient HRQoL data were enrolled. A good clinical outcome was represented by the modified Rankin Scale (mRS) 0 to 2. The patient's HRQoL was assessed using the Short Form health survey questionnaire, the Beck Depression Inventory, and the Daily Fatigue Impact Scale at 6 and 12 months. The results were analyzed regarding possible correlation to 24-hour urinary free cortisol, serum, and cerebrospinal fluid IL-6 levels.Results A reduction of HRQoL in up to 35% of survivors was observed at 6 months and in a high proportion of patients (47.2%) with an assumable good outcome (mRS 0–2). Reduced HRQoL in survivors was found in terms of SF-36 (34.9%), depression (26.8%), and fatigue (14%) at 6 months and 18.4%, 39.4%, and 18.9% at 12 months, respectively. Improvement was recorded at 12 months, mainly in SF-36. Early elevated 24-hour urinary free cortisol and IL-6 levels showed a significant positive impact on HRQoL.Conclusions Early cortisol and IL-6 levels may predict patients' HRQoL after SAH. Twelve months after SAH, a considerable percentage of patients with a presumably good outcome (mRS 0–2) had a lower HRQoL compared with the general population. Implementing corresponding tests at discharge and 12-month follow-up is recommended.
Keywords: health-related quality of life; subarachnoid hemorrhage; neurosurgery; vascular